Negative electrode sheet and method for producing the same, secondary battery, battery module, battery pack, and power consumption device
Patent Information
- Application Number
- JP2023554048
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-05-26
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-05-26
AI Technical Summary
【0028】 本願における1つ又は複数の実施例の詳細は、以下の図面及び説明に記載されており、本願の他の特徴、目的及び利点は明細書、図面及び特許請求の範囲から明らかになる。
Smart Images

Figure 0007640727000005 
Figure 0007640727000006 
Figure 0007640727000007
Abstract
Description
[Technical field]
[0001] The present application relates to the field of secondary batteries, in particular to a negative electrode sheet and its manufacturing method, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]
[0002] The negative electrode material of secondary batteries such as lithium-ion batteries is generally carbon materials such as natural graphite and artificial graphite, but the capacity of carbon materials is already approaching its theoretical capacity (372mAh / g), so the increase in the capacity of secondary batteries is limited. Silicon, as one of the negative electrode materials for secondary batteries, has a high theoretical capacity (4200mAh / g), is environmentally friendly, and has abundant reserves, and has attracted wide attention. However, the large volume change due to lithium insertion and extraction and the unstable solid electrolyte film formed on the surface cause deterioration of the silicon-containing negative electrode sheet during the charge and discharge process, and the cycle stability is poor, so the application of the silicon-containing negative electrode sheet in secondary batteries is limited. Summary of the Invention [Problem to be solved by the invention]
[0003] In view of the above problems, the present application provides a negative electrode sheet capable of reducing the volume expansion of the negative electrode sheet and improving the cycle characteristics of the negative electrode sheet, a manufacturing method thereof, a secondary battery, a battery module, a battery pack, and a power consuming device. [Means for solving the problem]
[0004] According to one aspect of the present application, a negative electrode current collector and a first negative electrode active material layer are included, the first negative electrode active material layer is provided on at least one surface of the negative electrode current collector, The components of the first negative electrode active material layer, calculated in mass %, include 30% to 70% of a silicon-based material, 15% to 40% of a binder, and 15% to 40% of a conductive agent, to provide a negative electrode sheet.
[0005] The above-mentioned negative electrode sheet has a reasonable mixing ratio of the components of the first negative electrode active material layer, which reduces the volume expansion of the silicon-based material in the negative electrode sheet during charge-discharge cycles, thereby preventing deterioration of the negative electrode sheet and improving the cycle expansion rate and cycle life of the negative electrode sheet.
[0006] In some embodiments, the binder and the conductive agent form a porous conductive network, and the porous conductive network coats the silicon-based material.
[0007] In some embodiments, in a cross section perpendicular to the thickness direction of the first negative electrode active material layer, the area ratio of the silicon-based material to the porous conductive network is 1:(0.5 to 1.5).
[0008] In some embodiments, the silicon-based material comprises at least one of elemental silicon, silicon oxide, silicon carbon composite, silicon nitrogen composite, silicon alloy, and lithium pre-doped silicon oxide.
[0009] In some embodiments, the silicon-based material has a volumetric particle size distribution Dv50 of 1 μm to 15 μm.
[0010] In some embodiments, the silicon-based material has a volumetric particle size distribution Dv50 of 4 μm to 8 μm.
[0011] In some embodiments, the mass % of the silicon-based material in the components of the first negative electrode active material layer is 45% to 55%.
[0012] In some embodiments, the binder has a glass transition temperature of ≦25° C.
[0013] In some embodiments, the binder comprises at least one of styrene butadiene rubber, modified styrene butadiene rubber, an acrylic compound, and butadiene.
[0014] In some embodiments, the mass percentage of the binder in the components of the first negative electrode active material layer is 18% to 23%.
[0015] In some embodiments, the mass % of the conductive agent in the components of the first negative electrode active material layer is 25% to 35%.
[0016] In some embodiments, the conductive agent comprises at least one of superconducting carbon, acetylene black, ketjen black, conductive carbon black, graphene, carbon dots, carbon nanotubes, carbon nanofibers, and graphite.
[0017] In some embodiments, the conductive agent includes graphite, conductive carbon black, and carbon nanotubes.
[0018] In some embodiments, the weight percent of the graphite in the conductive agent is between 85% and 97%.
[0019] In some embodiments, the graphite has a volumetric particle size distribution Dv50 of 1 μm to 20 μm.
[0020] In some embodiments, the graphite has a volumetric particle size distribution Dv50 of 2 μm to 4 μm.
[0021] In some embodiments, the negative electrode sheet further comprises a second negative electrode active material layer, the second negative electrode active material layer comprising a second negative electrode active material, the second negative electrode active material comprising at least one of graphite, soft carbon, hard carbon, a tin-based material, lithium titanate, and a silicon-containing active material.
[0022] In some embodiments, the second negative electrode active material is graphite.
[0023] According to a second aspect, the present application provides a method for producing a method for manufacturing a semiconductor device comprising: preparing a silicon-based material, a conductive agent and a binder into a negative electrode paste; applying the negative electrode paste to at least one surface of a negative electrode current collector and drying the paste to produce a first negative electrode active material layer; The present invention further provides a method for producing a negative electrode sheet, wherein the components of the first negative electrode active material layer include, calculated by mass%, 30% to 70% of the silicon-based material, 15% to 40% of the binder, and 15% to 40% of the conductive agent.
[0024] According to a third aspect, the present application further provides a secondary battery including the above-mentioned negative electrode sheet or a negative electrode sheet manufactured based on the above-mentioned method for manufacturing a negative electrode sheet.
[0025] According to a fourth aspect, the present application further provides a battery module including the above-mentioned secondary battery.
[0026] According to a fifth aspect, the present application further provides a battery pack including the above battery module.
[0027] According to a sixth aspect, the present application further provides a power consuming device including at least one selected from the above secondary battery, the above battery module, or the above battery pack.
[0028] The details of one or more embodiments of the application are set forth in the drawings and description that follow, and other features, objects and advantages of the application will become apparent from the description, drawings, and claims. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. [Diagram 3] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 4] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6] 1 is a schematic diagram of a power consuming device that uses a secondary battery as a power source according to an embodiment of the present application. [Figure 7] 1 is a scanning electron microscope (SEM) photograph of a cross section of a negative electrode sheet according to Example 1 of the present application, where a indicates a silicon-based material and b indicates a porous conductive network. [Figure 8] 1 is a scanning electron microscope (SEM) photograph of a cross section of a negative electrode sheet according to Comparative Example 1 of the present application, in which c indicates a silicon-based material and d indicates a conductive agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] To better describe and illustrate the embodiments and / or examples of the invention disclosed herein, reference may be made to one or more drawings, in which additional details or examples used to illustrate the drawings should not be considered as limiting the scope of the disclosed invention, either the presently described embodiments and / or examples, or the best mode of those inventions as currently understood.
[0031] To facilitate understanding of the present application, the present application will now be described more fully with reference to the accompanying drawings, in which: FIG. 1 illustrates a preferred embodiment of the present application; however, the present application may be embodied in many different forms and is not limited to the embodiments set forth herein; rather, the purpose of providing these embodiments is to provide a thorough and complete understanding of the present disclosure.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. The terms used in the present specification are merely for the purpose of describing specific examples and are not intended to be limiting of the present specification. The term "and / or" used herein includes any and all combinations of one or more of the associated listed items.
[0033] As the negative electrode active material of conventional secondary batteries, the capacity of carbon materials is already approaching its theoretical capacity (372mAh / g), so the increase in the capacity of secondary batteries is limited. Silicon has a high theoretical capacity (4200mAh / g), so it is promising as a new generation negative electrode active material to increase the capacity of secondary batteries. However, silicon-based materials have a high volume effect, and when used in negative electrode sheets, the large volume expansion during the cycle process causes problems such as film peeling, powdering, and wrinkles of the polar sheet, and the performance deterioration is serious. Therefore, in most cases, they are only used by mixing with carbon materials, and the usage ratio of silicon-based materials is greatly limited, and the silicon content is generally less than 15wt%.
[0034] As a result of research and invention by the inventors of the present application, by providing a negative electrode active material layer containing 30wt%~70wt% silicon-based material and increasing the amount of binder and conductive agent in the negative electrode active material layer, the volume expansion of silicon during charging can be effectively reduced, and the irreversible volume change of the negative electrode sheet can be reduced, so that the negative electrode sheet has a low cycle expansion rate and a long cycle life. In addition, the high content of silicon in the negative electrode active material layer can improve the energy density of the negative electrode sheet.
[0035] The present application provides a negative electrode sheet and a manufacturing method thereof, and a secondary battery, a battery module, a battery pack, and a power consuming device using the negative electrode sheet. Such a secondary battery is applicable to various power consuming devices using a battery, such as mobile phones, mobile devices, notebook computers, electric cars, electric toys, electric tools, electric vehicles, ships, and spacecraft, and spacecraft includes airplanes, rockets, space shuttles, and spaceships.
[0036] According to one embodiment of the present application, there is provided a negative electrode sheet including a negative electrode current collector and a first negative electrode active material layer.
[0037] The first negative electrode active material layer is provided on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposing each other in the thickness direction of the negative electrode current collector, and the first negative electrode active material layer is provided on either one or both of the two opposing surfaces of the negative electrode current collector.
[0038] Calculated by mass %, the components of the first negative electrode active material layer include 30% to 70% of a silicon-based material, 15% to 40% of a binder, and 15% to 40% of a conductive agent.
[0039] The above-mentioned negative electrode sheet has a reasonable mixing ratio of the components of the first negative electrode active material layer, which reduces the volume expansion of the silicon-based material in the negative electrode sheet during charge-discharge cycles, thereby preventing deterioration of the negative electrode sheet and improving the cycle expansion rate and cycle life of the negative electrode sheet.
[0040] Preferably, the mass % of the silicon-based material in the first negative electrode active material layer is 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%. More preferably, the mass % of the silicon-based material in the first negative electrode active material layer is 45% to 55%. When the mass % of the silicon-based material is within the above range, the overall performance of the negative electrode sheet is better.
[0041] Since the first negative electrode active material layer contains a silicon-based material at a mass % of 30% to 70%, in order to maintain good mechanical properties, it is necessary to use a high content of binder to suppress the volume expansion of the silicon-based material during charging and discharging. If the binder content is too low, the expansion suppression ability becomes relatively weak, and if the binder content is too high, it affects the conductive performance of the negative electrode sheet and increases the internal resistance of the polar sheet. Preferably, the mass % of the binder in the components of the first negative electrode active material layer is 15%, 20%, 25%, 30%, 35% or 40%. More preferably, the mass % of the binder in the components of the first negative electrode active material layer is 18% to 23%.
[0042] The silicon-based material and the binder in the first negative electrode active material layer both have low electrical conductivity, and it is necessary to improve the electrical conductivity of the negative electrode sheet by using a conductive agent to reduce the internal resistance of the negative electrode sheet. Preferably, the mass % of the conductive agent in the components of the first negative electrode active material layer is 15%, 20%, 25%, 30%, 35% or 40%. More preferably, the mass % of the conductive agent in the components of the first negative electrode active material layer is 25% to 35%.
[0043] In some embodiments, the binder and the conductive agent form a porous conductive network, and the porous conductive network covers the silicon-based material. The porous conductive network formed by the binder and the conductive agent covers the silicon-based material, so that the volume expansion of the silicon-based material during charging can be effectively reduced, and the porous conductive network has good mechanical properties and its structure is not easily destroyed by the expansion of the silicon-based material due to the high binder content, and at the same time, the porous conductive network shrinks during discharging, so that the irreversible volume change of the negative electrode sheet is greatly reduced. The porous conductive network formed by the binder and the conductive agent further has high conductive performance, and can effectively improve the problem of increased internal resistance caused by the high content of the silicon-based material and the binder. In addition, the porous conductive structure can further accelerate the infiltration of the electrolyte and improve the ionic conductivity of the polar sheet.
[0044] In some embodiments, in a cross section perpendicular to the thickness direction of the first negative electrode active material layer, the area ratio of the silicon-based material to the porous conductive network is 1: (0.5 to 1.5). The area ratio of the silicon-based material to the porous conductive network is obtained by analyzing a scanning electron microscope (SEM) photograph of the cross section of the polar sheet. By controlling the area ratio of the silicon-based material to the porous conductive network within the above range, the irreversible volume change of the negative electrode sheet is reduced, and good cycle stability is obtained. Preferably, in a cross section perpendicular to the thickness direction of the first negative electrode active material layer, the area ratio of the silicon-based material to the porous conductive network is 1: 0.5, 1: 0.6, 1: 0.7, 1: 0.8, 1: 0.9, 1: 1.0, 1: 1.2, or 1: 1.5. More preferably, in a cross section perpendicular to the thickness direction of the first negative electrode active material layer, the area ratio of the silicon-based material to the porous conductive network is 1: (1.1 to 1.5).
[0045] In some embodiments, the silicon-based material includes at least one of elemental silicon, silicon oxide, silicon carbon composite, silicon nitrogen composite, silicon alloy, and lithium pre-doped silicon oxide.
[0046] In some embodiments, the volumetric particle size distribution Dv50 of the silicon-based material is 1 μm to 15 μm. Dv50 refers to the particle size corresponding to 50% of the volume distribution. For example, Dv50 can be easily measured using a laser particle size analyzer such as the Mastersizer 2000E laser particle size analyzer of Malvern, UK, referring to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method. By controlling the volumetric particle size distribution Dv50 of the silicon-based material within the above range, the production of the paste of the negative electrode sheet is facilitated. If the Dv50 of the silicon-based material is too small, it is disadvantageous for the production of the paste, and if the Dv50 of the silicon-based material is too large, its conductive performance is deteriorated. Preferably, the volumetric particle size distribution Dv50 of the silicon-based material is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm. More preferably, the volumetric particle size distribution Dv50 of the silicon-based material is 4 μm to 8 μm.
[0047] In some embodiments, the binder comprises a flexible binder having a glass transition temperature ≦25° C. By selecting and using a flexible binder having a low glass transition temperature, it can be in a highly elastic state over a relatively wide temperature range, and in combination with a silicon-based material having a high elastic limit and a large breaking elongation, which has a large volume change, the volume expansion of the negative electrode sheet can be effectively controlled.
[0048] In some embodiments, the flexible binder comprises at least one of styrene butadiene rubber, modified styrene butadiene rubber, an acrylic compound, and butadiene. Specifically, the acrylic compound preferably comprises at least one selected from methyl acrylate, ethyl acrylate, butyl acrylate, and lauryl acrylate.
[0049] In some embodiments, the binder further comprises a hard binder having a glass transition temperature >25° C. The hard binder having a glass transition temperature higher than 25° C. has high strength and can significantly suppress the expansion and pulverization of the silicon-based material, and the negative electrode sheet has suitable flexibility, so that the first negative electrode active material layer does not crack or peel off.
[0050] In some embodiments, the hard binder comprises at least one of polyacrylic acid (PAA), polyacrylonitrile (PAN), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0051] In some embodiments, the binder comprises 90% to 100% of a flexible binder and 0 to 10% of a hard binder, calculated by mass %, By controlling the blending ratio of the binder within the above range, the cycle expansion rate of the negative electrode sheet is low and the cycle characteristics are better.
[0052] In some embodiments, the conductive agent comprises at least one of superconducting carbon, acetylene black, ketjen black, conductive carbon black, graphene, carbon dots, carbon nanotubes, carbon nanofibers, and graphite.
[0053] More preferably, the conductive agent includes graphite, conductive carbon black and carbon nanotubes. Conductive carbon black not only has good conductive performance, but also participates in lithium insertion and extraction. Carbon nanotubes have excellent conductive performance and a large aspect ratio, improving the conductive contact with silicon-based materials. Graphite also has excellent conductive performance and is relatively low in cost. The selection and use of graphite, conductive carbon black and carbon nanotubes as conductive agents is advantageous in improving the volume expansion of the negative electrode sheet and at the same time ensuring the conductive performance of the negative electrode sheet.
[0054] Graphite has good conductive performance, electrical and chemical properties, and low cost, and can be used as the main conductive agent. In some embodiments, the weight percent of graphite in the conductive agent is 85% to 97%.
[0055] Conductive carbon black is involved in the insertion and desorption of lithium during the charge and discharge process, but the reversible portion does not exceed 20%, so that the content of conductive carbon black is too high, which affects the cycle characteristics of the negative electrode sheet. In some embodiments, the mass% of conductive carbon black in the conductive agent is 1% to 14%.
[0056] Since carbon nanotubes have a linear structure and a tube diameter of less than 10 nm, if the amount of carbon nanotubes used is too large, it will affect the production of the paste and the processing performance will be poor. In some embodiments, the mass percentage of carbon nanotubes in the conductive agent is 0.5% to 6%.
[0057] As a result of the research by the inventors, it was found that the magnitude of the volumetric particle size distribution of graphite in the conductive agent significantly affects the conductive performance of the negative electrode sheet, and when the volumetric particle size distribution of graphite is large, the electrical resistance of the negative electrode sheet becomes relatively high, and when the volumetric particle size distribution of graphite is small, it is advantageous for the formation of a porous conductive network with good conductive performance, and the electrical resistance of the negative electrode sheet becomes relatively low. In some embodiments, the volumetric particle size distribution Dv50 of graphite is 1 μm to 20 μm. Preferably, the volumetric particle size distribution Dv50 of graphite is 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 16 μm, 18 μm, or 20 μm. More preferably, the volumetric particle size distribution Dv50 of graphite is 2 μm to 4 μm.
[0058] In some embodiments, the first negative electrode active material layer further comprises 0.5% to 2% of a dispersant, calculated by mass %. The dispersant can improve the dispersion distribution of the silicon-based material, the binder, and the conductive agent in the first negative electrode active material layer. Preferably, the mass % of the dispersant in the first negative electrode active material layer is 0.5%, 0.7%, 1%, 1.3%, 1.5%, 1.8%, or 2%. More preferably, the mass % of the dispersant in the first negative electrode active material layer is 0.8% to 1.2%.
[0059] In some embodiments, the dispersing agent comprises at least one of carboxymethylcellulose (CMC) and sodium carboxymethylcellulose (CMC-Na).
[0060] In some embodiments, the negative electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, a copper foil. The composite current collector can include a polymer substrate layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector can be formed by forming a metal material, such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, on a polymer substrate. The polymer substrate can be selected from substrates including polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), and the like.
[0061] In some embodiments, the negative electrode sheet preferably further comprises a second negative electrode active material layer, The second negative electrode active material layer includes a second negative electrode active material, the second negative electrode active material including at least one of graphite, soft carbon, hard carbon, a tin-based material, lithium titanate, and a silicon-containing active material.
[0062] Specifically, in the second negative electrode active material layer, the weight percent of the silicon-containing active material is <30%.
[0063] Preferably, the second negative electrode active material is graphite.
[0064] In some embodiments, the second negative electrode active material layer is provided between the first negative electrode active material layer and the negative electrode current collector, or the second negative electrode active material layer is provided on the surface of the first negative electrode active material layer remote from the negative electrode current collector. Preferably, the second negative electrode active material layer is provided on the surface of the first negative electrode active material layer remote from the negative electrode current collector. By providing the second negative electrode active material layer on the surface of the first negative electrode active material layer remote from the negative electrode current collector, the cycle expansion rate of the negative electrode sheet can be further reduced and the cycle characteristics of the battery can be improved.
[0065] As will be understood, the number of the second negative electrode active material layers is at least one, and at least one second negative electrode active material layer is provided on the surface of the first negative electrode active material layer away from the negative electrode current collector. As an example, when the number of the second negative electrode active material layers is n and n=1, the first negative electrode active material layer is provided on the surface of the current collector, and the second negative electrode active material layer is provided on the surface of the first negative electrode active material layer away from the negative electrode current collector, and when n>1, at least one second negative electrode active material layer is provided on the surface of the first negative electrode active material layer away from the negative electrode current collector. By adopting the above structure, it is possible to avoid providing the first negative electrode active material layer on the outer surface of the negative electrode sheet, thereby further reducing the cycle expansion rate of the negative electrode sheet and improving the cycle characteristics of the negative electrode sheet.
[0066] In some embodiments, the second negative electrode active material layer preferably further comprises a binder, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0067] In some embodiments, the second negative electrode active material layer preferably further comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0068] In some embodiments, the second negative electrode active material layer preferably includes other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0069] Another embodiment of the present application further provides a method for producing a negative electrode sheet, including the following steps S1 to S2.
[0070] In step S1, a silicon-based material, a conductive agent, and a binder are mixed to prepare a negative electrode paste.
[0071] In some embodiments, step S1 is specifically performed by uniformly dry-mixing the silicon-based material, the conductive agent, and the dispersant (30 wt% to 50 wt% of the total amount of the dispersant) using a vacuum mixer, adding deionized water and uniformly kneading the mixture, then adding the remaining dispersant and deionized water and uniformly stirring the mixture under vacuum, and then adding the binder and uniformly stirring the mixture under vacuum to obtain the negative electrode paste.
[0072] In step S2, the negative electrode paste is applied to at least one surface of the negative electrode current collector and dried to produce a first negative electrode active material layer. Calculated by mass%, the components of the first negative electrode active material layer include 30% to 70% of a silicon-based material, 15% to 40% of a binder, and 15% to 40% of a conductive agent.
[0073] In some embodiments, the composition of the first negative electrode active material layer further comprises 0.5% to 2% of a dispersant.
[0074] In some embodiments, the coating and drying process in step S2 is specifically performed by extruding the negative electrode paste onto the negative electrode current collector at a speed of 1 m / min to 4 m / min, and then baking the paste at 80° C. to 120° C. for 10 min to 20 min.
[0075] Hereinafter, a secondary battery, a battery module, a battery pack, and a power consuming device according to the present application will be described with reference to the drawings as appropriate.
[0076] In one embodiment of the present application, a secondary battery is provided.
[0077] In general, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the charging and discharging process of the battery, active ions shuttle between the positive electrode sheet and the negative electrode sheet to be inserted and removed. The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet. The separator is installed between the positive electrode sheet and the negative electrode sheet, and serves mainly to prevent short circuit between the positive and negative electrodes while allowing ions to pass through.
[0078] Negative electrode sheet The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer including a negative electrode active material and disposed on at least one surface of the negative electrode current collector. In the embodiment of the present application, the negative electrode sheet provided by the first aspect is used as the negative electrode sheet.
[0079] Positive electrode sheet The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer that contains a positive electrode active material and is disposed on at least one surface of the positive electrode current collector.
[0080] As an example, the positive electrode current collector has two surfaces opposing each other in the thickness direction, and the positive electrode active material layer is provided on one or both of the two opposing surfaces of the positive electrode current collector.
[0081] In some embodiments, the positive electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, an aluminum foil. The composite current collector can include a polymeric substrate layer and a metal layer formed on at least one surface of the polymeric substrate layer. The composite current collector can be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0082] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials in batteries may be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviated as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (abbreviated as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM 811 )), lithium nickel cobalt aluminum oxide (e.g. LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc., but are not limited thereto. The lithium-containing phosphate having an olivine structure may include, but is not limited to, at least one of, for example, lithium iron phosphate (e.g., LiFePO4 (abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.
[0083] In some embodiments, the positive electrode active material layer preferably further includes a binder. For example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0084] In some embodiments, the positive electrode active material layer preferably further includes a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0085] In some embodiments, the positive electrode sheet can be manufactured by the following method: Components for manufacturing the positive electrode sheet, such as a positive electrode active material, a conductive agent, a binder, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode paste, which is then applied to a positive electrode current collector, and the positive electrode sheet can be obtained through steps such as drying and cold pressing.
[0086] electrolyte The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet. The present application does not particularly limit the type of electrolyte, and it can be selected as needed. For example, the electrolyte may be liquid, gel, or completely solid.
[0087] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0088] In some examples, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bisoxalate borate, lithium difluorooxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0089] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0090] In some embodiments, the electrolyte preferably further includes an additive. For example, the additive may include an anode film-forming additive, a cathode film-forming additive, and may further include an additive capable of improving a specific characteristic of the battery, such as an additive for improving the overcharge characteristic of the battery, an additive for improving the high-temperature or low-temperature characteristic of the battery, etc.
[0091] Separator In some embodiments, the secondary battery further includes a separator. The present application does not particularly limit the type of the separator, and any known porous structure separator having good chemical stability and mechanical stability can be selected.
[0092] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a monolayer film or a multilayer composite film, and is not particularly limited. When the separator is a multilayer composite film, the materials of each layer can be the same or different, and is not particularly limited.
[0093] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be fabricated into an electrode assembly via a winding or lamination process.
[0094] In some embodiments, the secondary battery can include a housing material, which is used to encapsulate the electrode assembly and the electrolyte.
[0095] In some embodiments, the exterior material of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior material of the secondary battery may be a soft pack, such as a pouch-type soft pack, etc. The material of the soft pack may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0096] The present application does not particularly limit the shape of the secondary battery, and the secondary battery may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows a secondary battery 5 having a rectangular structure as an example.
[0097] In some embodiments, referring to FIG. 2, the exterior material may include a housing 51 and a cover plate 53. The housing 51 includes a bottom plate and a side plate connected to the bottom plate, and a receiving cavity surrounded by the bottom plate and the side plate is formed. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The electrode assembly 52 may be formed from a positive electrode sheet, a negative electrode sheet and a separator through a winding process or a lamination process. The electrode assembly 52 is sealed in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and can be selected by those skilled in the art according to specific practical requirements.
[0098] In some embodiments, the secondary batteries can be assembled into a battery module, and the number of secondary batteries included in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0099] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, a plurality of secondary batteries 5 can be arranged in sequence along the length direction of the battery module 4. Of course, any other arrangement may be used. The plurality of secondary batteries 5 can be fixed by fasteners.
[0100] Preferably, the battery module 4 may further include an outer case having an accommodation space in which the plurality of secondary batteries 5 are accommodated.
[0101] In some embodiments, the battery modules can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0102] 4 and 5 show an example of a battery pack 1. Referring to Fig. 4 and Fig. 5, the battery pack 1 may include a battery case and a plurality of battery modules 4 installed in the battery case. The battery case includes an upper housing 2 and a lower housing 3, and the upper housing 2 may be placed over the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery case in any manner.
[0103] The present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage element for the power consuming device. The power consuming device may include, but is not limited to, a mobile device, an electric vehicle, a train, a ship, a satellite, an energy storage system, and the like. The mobile device may be, for example, a mobile phone, a laptop, and the like, and the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, and the like, but is not limited to these.
[0104] As the power consuming device, a secondary battery, a battery module or a battery pack can be selected according to the usage requirements.
[0105] 6 is an example of a power consumption device 6. The power consumption device 6 may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements for the secondary battery of the power consumption device, a battery pack or a battery module may be used.
[0106] Other examples of the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such devices are generally required to be lightweight and thin, and can use a secondary battery as a power source.
[0107] Working Example The following is a description of the examples of the present application. The examples described below are illustrative and are only intended to explain the present application, and should not be understood as limiting the present application. If no specific techniques or conditions are shown in the examples, they are carried out according to the techniques or conditions described in the literature in this field, or according to the product instructions. If no manufacturer is listed for the reagents or equipment used, they are all commercially available general products.
[0108] Example 1: Preparation of negative electrode sheet of Example 1: Silicon monoxide (SiO), binder, dispersant (CMC-Na), and conductive agent are thoroughly stirred and mixed in deionized water in a mass ratio of 45%:20.4%:1.2%:33.4% to prepare a negative electrode paste. Dv50 of silicon monoxide is 6.8 μm, and binder is styrene butadiene rubber (SBR) and polyacrylic acid (PAA) in a mass ratio of 94%:6%. Conductive agent is artificial graphite, conductive carbon black (Super-P, SP), and carbon nanotube (CNT) in a mass ratio of 96.1%:3%:0.9%, and Dv50 of artificial graphite is 3.5 μm. The above paste is uniformly applied on a copper current collector with a thickness of 8 μm by extrusion coating, and after drying, cold pressing, and cutting, the green density is 1.65 g / cm. 3 , coating weight 5.19mg / cm 2 A negative electrode sheet of
[0109] Referring to FIG. 7, this is a scanning electron microscope (SEM) image of the cross section of the negative electrode sheet of Example 1, in which the silicon-based material (a) and the porous conductive network (b) of the first negative electrode active material layer can be observed, the porous conductive network has a rich pore structure, and the particles of the silicon-based material are dispersed within the porous conductive network.
[0110] The compositional blend ratios of the negative electrode sheets of Examples 1 to 25 and Comparative Examples 1 to 4 are recorded in Table 1.
[0111] [Table 1] TIFF0007640727000002.tif235168TIFF0007640727000003.tif214168
[0112] Examples 2 to 7: The negative electrode sheets of Examples 2 to 7 differ from Example 1 in that the mass ratios of silicon monoxide, binder, and conductive agent are different.
[0113] Example 8: Example 8 differs from Example 1 in that the binder is a mixture of styrene butadiene rubber (SBR) and polyacrylic acid (PAA) in a mass ratio of 90%:10%.
[0114] Example 9: Example 9 differs from Example 1 in that the binder is styrene butadiene rubber (SBR).
[0115] Example 10: Example 10 differs from Example 1 in that the binder is a mixture of styrene butadiene rubber (SBR) and polyacrylic acid (PAA) in a mass ratio of 80%:20%.
[0116] Examples 11 to 13: Examples 11 to 13 differ from Example 1 in that the Dv50 of the silicon monoxide is different.
[0117] Examples 14 to 16: Examples 14 to 16 differ from Example 1 in that the Dv50 of the artificial graphite in the conductive agent is different.
[0118] Example 17: Example 17 differs from Example 1 in that the conductive agent is artificial graphite of 3.5 μm.
[0119] Example 18: Example 18 differs from Example 1 in that the conductive agent is conductive carbon black (Super-P, SP).
[0120] Examples 19 to 23: Examples 19 to 23 differ from Example 1 in that the compounding ratio of artificial graphite, conductive carbon black (Super-P, SP), and carbon nanotubes (CNT) in the conductive agent is different.
[0121] Example 24: Preparation of negative electrode sheet of Example 24: First negative electrode paste: Silicon monoxide, binder, dispersant (CMC-Na), and conductive agent are thoroughly mixed in deionized water in a mass ratio of 45%:20.4%:1.2%:33.4% to prepare a first negative electrode paste. Silicon monoxide has a Dv50 of 6.8 μm, and the binder is styrene butadiene rubber (SBR) and polyacrylic acid (PAA) in a mass ratio of 94%:6%. The conductive agent is artificial graphite, conductive carbon black (Super-P, SP), and carbon nanotubes (CNT) in a mass ratio of 96.1%:3%:0.9%, and the artificial graphite has a Dv50 of 3.5 μm.
[0122] Second negative electrode paste: Artificial graphite, binder (SBR), dispersant (CMC-Na), conductive carbon black (Super-P, SP) are thoroughly mixed in deionized water in a mass ratio of 96.2%:1.8%:1.2%:0.8% to prepare a second negative electrode paste, and the Dv50 of the artificial graphite is 14.3 μm.
[0123] Using a double cavity extrusion coating device, the first negative electrode paste is uniformly coated on a copper current collector with a thickness of 8 μm to form a first negative electrode active material layer, and at the same time, the second negative electrode paste is uniformly coated on the first negative electrode active material layer to form a second negative electrode active material layer. After drying, cold pressing and cutting, the green density is 1.65 g / cm 3 , coating weight 8.37mg / cm 2 The mass ratio of silicon monoxide in the negative electrode sheet active material layer was 15%.
[0124] Example 25: Example 25 differs from Example 24 in that the second negative electrode paste of Example 24 is applied onto a current collector to form a second negative electrode active material layer, the first negative electrode paste of Example 24 is applied onto the second negative electrode active material layer to form a first negative electrode active material layer, the components are not changed, and the mass ratio of silicon monoxide to the polar sheet coating layer is 15%.
[0125] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that the mass ratio of the binder is 2.3%, the mass ratio of the conductive agent is 51.5%, and the mass ratio of SBR to PAA is 65.2%:34.8%. The composition of the negative electrode sheet of Comparative Example 1 is a typical blend ratio of a conventional silicon-containing negative electrode sheet.
[0126] Referring to FIG. 8, this is a scanning electron microscope (SEM) image of a cross section of the negative electrode sheet of Comparative Example 1, in which a silicon-based material (c) and a conductive agent (d, mainly graphite) can be observed in the first negative electrode active material layer, and a small amount of binder is dispersed in the first negative electrode active material layer, making it difficult to observe its distribution. Unlike the negative electrode sheet of Example 1, the conductive agent in the negative electrode sheet of Comparative Example 1 is distributed in a block shape, and no porous structure can be observed.
[0127] Comparative Example 2: Comparative Example 2 differs from Example 1 in that the mass ratio of the binder is 48.8% and the mass ratio of the conductive agent is 5%.
[0128] Comparative Example 3: Comparative Example 3 differs from Example 1 in that the mass ratio of silicon monoxide is 15%, the mass ratio of the binder is 2.3%, the mass ratio of the conductive agent is 81.5%, and the mass ratio of SBR to PAA is 65.2%:34.8%.
[0129] Comparative Example 4: Comparative Example 4 differs from Example 24 in that the first negative electrode paste applied to the surface of the current collector has the same composition as the paste of Comparative Example 1, the other components are unchanged, and the mass ratio of silicon monoxide to the polar sheet active material layer is 15%.
[0130] Positive electrode sheet manufacturing: Positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are dissolved in the solvent N-methylpyrrolidone (NMP) in a mass ratio of 97%:1.5%:1.5%, and thoroughly mixed to produce a positive electrode paste. The positive electrode paste is then evenly applied to the aluminum foil of the positive electrode current collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0131] Separator: Use polypropylene film.
[0132] Electrolyte preparation: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte solution, in which the concentration of LiPF6 is 1 mol / L.
[0133] Secondary battery manufacturing: The positive electrode sheet, the separator, and the negative electrode sheet are laminated in this order and wound to obtain an electrode assembly, which is then placed in an outer casing, and the above-prepared electrolyte is added. A secondary battery is obtained through processes such as sealing, standing, chemical formation, and aging.
[0134] Test section: Analysis of cross-sectional shape of negative electrode sheet by ion milling (CP): Argon gas is ionized to generate argon ions, which are then accelerated and focused before colliding with atoms or molecules on the sample surface to achieve ion milling, to produce a cross-sectional sample of the negative electrode sheet. A scanning electron microscope (SEM) (such as ZEISS Sigma 300) is used to photograph the cross-section of the negative electrode sheet. Reference standard: JY / T010-1996 "General Principles of Analytical Scanning Electron Microscope Methods". The area ratio of the silicon-based material in the image per unit area is analyzed and calculated, and the remaining part is taken as the porous conductive network, to calculate the area ratio of the silicon-based material to the porous conductive network.
[0135] Secondary battery internal resistance test: The internal resistance of the secondary battery is measured using a battery internal resistance measuring device (Anpico model ATS21). After clamping the probes of the battery internal resistance measuring device to the polarity columns on both sides of the secondary battery for 5 seconds, the resistance value is read after the numbers on the measuring device have stabilized.
[0136] Cycle characteristic test of secondary battery at 45℃: The secondary battery is charged at a constant current of 1C in a constant temperature environment of 45°C until the voltage reaches 4.25V, then charged at a constant voltage of 4.25V until the current falls to 0.05C or less, and then allowed to stand for 5 minutes, and then discharged at a constant current of 1C until the voltage reaches 2.5V, and allowed to stand for 5 minutes, which is one cycle of charge and discharge process, and the discharge capacity at this time is recorded as the discharge capacity of the first cycle of the secondary battery. The secondary battery is subjected to a cycle charge and discharge test according to the above method until the cell capacity is attenuated to 80%, and the number of cycles is recorded.
[0137] Full charge cycle expansion performance test of polar sheet of secondary battery at 45℃: The thickness of the sheet when the cold pressing process of the negative electrode sheet of the secondary battery is completed is recorded as h0. Based on the above-mentioned cycle characteristic test method of the secondary battery at 45 ° C., the secondary battery is cycled 100 times, charged at a constant current of 1 C until the voltage reaches 4.25 V, and then charged at a constant voltage of 4.25 V until the current becomes 0.05 C or less, and then left to stand for 5 minutes, at which point the cell is in a fully charged state. The cell after cycling is then disassembled in a drying room, and the thickness of the negative electrode sheet after 100 cycles is recorded as h100. 満充 The expansion rate Δh100 of the polar sheet of the secondary battery at 45°C for 100 full charge cycles 満充 (%)=(h100 満充 -h0) / h0*100%.
[0138] Irreversible cycle expansion performance test of polar sheet of secondary battery at 45℃: The thickness of the negative electrode sheet of the secondary battery when the cold pressing process is completed is recorded as h0. Based on the cycle characteristic test method of the secondary battery at 45 ° C., the secondary battery is cycled 100 times, discharged at a rate of 0.1 C to 2.5 V, and then left to stand for 5 minutes. Then, the cell after the cycle is disassembled in a drying room, and the thickness of the negative electrode sheet after 100 cycles is recorded as h100. 満放 The irreversible cycle expansion rate Δh100 of the polar sheet of the secondary battery at 45°C for 100 cycles 不可逆 (%)=(h100 満放 -h0) / h0*100%.
[0139] [Table 2]
[0140] As can be seen from the related data in Table 2, in the secondary batteries of Examples 1 to 22, the area ratio of the silicon-based material to the porous conductive network on the cross section of the negative electrode sheet was 1:(0.8 to 1.5), the internal resistance of the secondary battery was 6 mΩ to 8 mΩ, the number of cycles at which the capacity was attenuated to 80% was 427 to 720, the full charge cycle expansion rate at 100 cycles was 71% to 150.1%, and the irreversible cycle expansion rate at 100 cycles was 14% to 33.2%.
[0141] The internal resistance of the secondary battery in Comparative Example 1 is 6.3mΩ, the number of cycles when the capacity is attenuated to 80% is 312, the full charge cycle expansion rate at 100 cycles is 189%, and the irreversible cycle expansion rate at 100 cycles is 106%. Compared with the conventional silicon-containing negative electrode sheet in Comparative Example 1, the secondary batteries according to the compositions of the negative electrode sheets in Examples 1 to 22 have an internal resistance close to that of Comparative Example 1, the cycle characteristics are better than those of the secondary battery in Comparative Example 1, and the full charge cycle expansion rate and the irreversible cycle expansion rate are both lower than those of Comparative Example 1, which indicates that the negative electrode sheet provided by the present application used in Examples 1 to 22 can effectively control the cycle expansion of the negative electrode sheet, and the lower irreversible cycle expansion rate indicates that the volume expansion of silicon in the negative electrode sheet causes less irreversible deterioration of the negative electrode sheet, and therefore the secondary batteries in Examples 1 to 22 have good cycle characteristics.
[0142] The negative electrode paste of Example 23 contains a large amount of CNTs. If this is used to manufacture a negative electrode paste, the paste will be difficult to disperse, which is disadvantageous for manufacturing a negative electrode sheet.
[0143] In the secondary batteries of Examples 24 and 25, the internal resistance of the secondary battery is 6.4 mΩ to 6.5 mΩ, the number of cycles at which the capacity is attenuated to 80% is 818 to 1123, the full charge cycle expansion rate at 100 cycles is 48.1% to 48.4%, and the irreversible cycle expansion rate at 100 cycles is 9.8% to 10.2%. In the negative electrode sheet, by combining a first negative electrode active material layer containing silicon and a second negative electrode active material layer of pure graphite, the cycle expansion rate of the secondary battery is lower and the cycle characteristics are good. In particular, in Example 24, the first negative electrode active material layer containing silicon is provided between the negative electrode current collector and the second negative electrode active material layer, and the cycle characteristics are better.
[0144] Compared with Example 1, the negative electrode sheet of Comparative Example 2 has a binder mass content of 48.8%, and the cycle expansion rate (full charge cycle expansion rate and irreversible cycle expansion rate) of the secondary battery of Comparative Example 2 is obviously higher than that of the secondary battery of Comparative Example 1. However, since the binder content is too high, the internal resistance of the secondary battery increases, resulting in poor cycle characteristics.
[0145] In the negative electrode sheet of Comparative Example 3, a conductive agent (mainly graphite) was used to replace part of the silicon monoxide, the binder mixing ratio was the same as in Comparative Example 1, and the silicon monoxide content was the same as in the negative electrode sheet of Examples 24 and 25. However, the cycle expansion rate was obviously higher than that of Examples 24 and 25, and the cycle characteristics were also lower than those of Examples 24 and 25.
[0146] The difference between Comparative Example 4 and Example 24 is the compounding ratio of the first negative electrode active material layer, and the number of cycles when the secondary battery capacity of Comparative Example 4 was attenuated to 80% was 453, the full charge cycle expansion rate at 100 cycles was 84.3%, and the irreversible cycle expansion rate at 100 cycles was 43.1%. As can be seen from the above, when the negative electrode sheet has a two-layer active material layer structure, the first negative electrode active material layer manufactured with the compounding ratio of the conventional silicon-containing active material layer has significant volume expansion, and when combined with a pure graphite negative electrode active material layer, the cycle characteristics are improved compared to the secondary battery of Comparative Example 1, but are clearly inferior to Example 24.
[0147] The technical features of the above embodiments can be combined in any manner, and for the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, any combination should be considered within the scope described in this specification.
[0148] The above examples merely show some embodiments of the present application, and the description is specific and detailed, but should not be understood as limiting the scope of the claims of the invention. It should be noted that those skilled in the art can make some modifications and improvements without departing from the concept of the present application, and all of them should be considered as the scope of protection of the present application. Therefore, the scope of protection of the patent of the present application should be based on the scope of the attached claims. [Explanation of symbols]
[0149] 1 Battery pack 2 Upper case 3 Lower case 4 Battery Module 5 Secondary battery 51 Housing 52 Electrode Assembly 53 Cover plate 6 Power consumption equipment
Claims
1. a negative electrode current collector; and a first negative electrode active material layer, the first negative electrode active material layer is provided on at least one surface of the negative electrode current collector, Calculated by mass%, the components of the first negative electrode active material layer include 30% to 70% of a silicon-based material, 15% to 40% of a binder, and 15% to 40% of a conductive agent; A negative electrode sheet, characterized in that the binder and the conductive agent form a porous conductive network, and the porous conductive network covers the silicon-based material.
2. 2. The negative electrode sheet according to claim 1, wherein in a cross section perpendicular to a thickness direction of the first negative electrode active material layer, an area ratio of the silicon-based material to the porous conductive network is 1:(0.5 to 1.5).
3. 2. The negative electrode sheet according to claim 1, wherein the silicon-based material comprises at least one of elemental silicon, silicon oxide, silicon carbon composite, silicon nitrogen composite, silicon alloy, and lithium pre-doped silicon oxide.
4. The negative electrode sheet according to claim 1, wherein the silicon-based material has a volumetric particle size distribution Dv50 of 1 μm to 15 μm.
5. The negative electrode sheet according to claim 1, wherein the silicon-based material has a volumetric particle size distribution Dv50 of 4 μm to 8 μm.
6. The negative electrode sheet according to claim 1 , wherein the mass percentage of the silicon-based material in the first negative electrode active material layer is 45% to 55%.
7. The negative electrode sheet according to claim 1 , wherein the binder has a glass transition temperature of ≦25° C.
8. The negative electrode sheet according to claim 7 , wherein the binder comprises at least one of styrene-butadiene rubber, modified styrene-butadiene rubber, an acrylic compound, and butadiene.
9. The negative electrode sheet according to claim 1 , wherein the mass percentage of the binder in the first negative electrode active material layer is 18% to 23%.
10. The negative electrode sheet according to claim 1 , wherein the conductive agent is present in an amount of 25% to 35% by mass in the first negative electrode active material layer.
11. The negative electrode sheet according to claim 1 , wherein the conductive agent comprises at least one of superconducting carbon, acetylene black, ketjen black, conductive carbon black, graphene, carbon dots, carbon nanotubes, carbon nanofibers, and graphite.
12. The negative electrode sheet according to claim 1 , wherein the conductive agent comprises graphite, conductive carbon black, and carbon nanotubes.
13. The negative electrode sheet according to claim 12, wherein the mass percentage of the graphite in the conductive agent is 85% to 97%.
14. The negative electrode sheet according to claim 11, wherein the graphite has a volumetric particle size distribution Dv50 of 1 μm to 20 μm.
15. The negative electrode sheet according to claim 11, wherein the graphite has a volumetric particle size distribution Dv50 of 2 μm to 4 μm.
16. 2. The negative electrode sheet according to claim 1, further comprising a second negative electrode active material layer including a second negative electrode active material, the second negative electrode active material including at least one of graphite, soft carbon, hard carbon, a tin-based material, lithium titanate, and a silicon-containing active material.
17. The negative electrode sheet according to claim 16, wherein the second negative electrode active material is graphite.
18. preparing a silicon-based material, a conductive agent and a binder into a negative electrode paste; applying the negative electrode paste to at least one surface of the negative electrode current collector and drying the paste to produce a first negative electrode active material layer; Calculated by mass%, the components of the first negative electrode active material layer include 30% to 70% of the silicon-based material, 15% to 40% of the binder, and 15% to 40% of the conductive agent; A method for producing a negative electrode sheet, characterized in that the binder and the conductive agent form a porous conductive network, and the porous conductive network covers the silicon-based material.
19. A secondary battery comprising the negative electrode sheet according to claim 1.
20. A battery module comprising the secondary battery according to claim 19.
21. A battery pack comprising the battery module according to claim 20.
22. A power consuming device comprising at least one selected from the group consisting of the secondary battery according to claim 19, the battery module according to claim 20, and the battery pack according to claim 21.
Citation Information
Patent Citations
Silicon-based negative electrode plate, fabrication method thereof and lithium ion battery
CN109888266A
Nonaqueous electrolyte battery
JP2007035434A
Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2013229163A
Negative electrode and power storage device
JP2015179592A
Carbon composite silicon material and manufacturing method therefor, and negative electrode material for lithium secondary batteries
JP2016028375A